Exploring the Role of Innovative Technologies in Smart Cities - Kagontle Selwe; Costa Hofisi (Journal of Education and Learning Technology)
Smart cities emerged as a solution to simplify the lives of urban citizens by integrating Information and Communication Technologies (ICTs) into daily operations and addressing the rapid urbanisation challenge. This article relied on an extensive literature review to explore the role of innovative technologies such as smart traffic management, smart buildings and smart healthcare in the development of smart cities. It further explored the policy, legal, and institutional frameworks that underpin the development and operation, including strategies for protecting and handling citizen data while also addressing both cybersecurity threats from cyberattacks and the privacy of citizens within these intelligent urban environments. The article identified the unique challenges posed by the very nature of smart city networks which include Cybersecurity Risks and Data Privacy Concerns. Despite the promising potential of smart city technologies to create a more efficient, sustainable, and citizen-focused urban environment, the challenges identified in this article should be addressed in order to unlock the full potential of innovative technologies for smart cities.